Effects of Maternal Pb2+ poisoning during pregnancy on the development of the jaw (Meckel´s Cartilage) of rat fetus - Brandini, Daniela Atili [UNESP]; Sala, Miguel Angel; Lopes, Ruberval Armando (My University, 2011)
The purpose of this study was to investigate the effects of maternal lead poisoning during pregnancy on the development of the jaw (Meckel's cartilage) of rat fetuses by histologic and morphometric methods. Pregnant rats received a single intraperitoneal injection of 2.5 mg of lead acetate/100g body weight on the 10th day of pregnancy. Meckel's cartilage of fetuses of the lead-treated group showed smaller volume density and size of the lacunae, as well as modification of the lacunae shape. Moreover, the number density of lacunae and the volume density of the matrix increased significantly in the Meckel's cartilage in treated group fetuses. The results suggest that lead poisoning during the period of organogenesis can induce disturbances in the development and differentiation of the fetal stomatognathic system. Reducing the consumption of alcoholic beberages and smoking cessation by women in childbearing age, along with a strict policy of control of the environmental lead exposure can bring great benefits to the future generations of children.